"In vivo" amplification of biological activity of tetragastrin by amino acid hydroxamates. Issue 12 (December 1984) - Bali, J. P.; Mattras, H.; Previero, A.; Coletti-Previero, M. A.
Abstract : Rat blood was shown to contain an aminopeptidase which rapidly hydrolyses short peptides containing an aromatic amino acid as N-terminal residue. Using tetragastrin (Trp-Met-Asp-PheNH 2) as substrate, we showed that some amino acid hydroxamates inhibit rat aminopeptidase activity 'in vitro' in the following order: HTrpNHOH > HPheNHOH ≫ HAIaNHOH. The same hydroxamates markedly enhanced the biological activity of tetragastrin 'in vivo'. The amplification of the secretory effect, correlated with the amount of the hydroxamate used, strongly suggests that these compounds can stabilize a number of active peptides in vivo by inhibiting their proteolytic degradation.